2016
DOI: 10.1021/acs.jctc.6b00193
|View full text |Cite
|
Sign up to set email alerts
|

Insights into How Cyclic Peptides Switch Conformations

Abstract: Cyclic peptides have recently emerged as promising modulators of protein-protein interactions. However, it is currently highly difficult to predict the structures of cyclic peptides owing to their rugged conformational free energy landscape, which prevents sampling of all thermodynamically relevant conformations. In this article, we first investigate how a relatively flexible cyclic hexapeptide switches conformations. It is found that, although the circular geometry of small cyclic peptides of size 6-8 may req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 94 publications
0
78
0
Order By: Relevance
“…The conformations of cyclic hexapeptides have been studied extensively. Usually, cyclic hexapeptides acquire well-defined backbone structures and cyclic hexapeptides containing trans-amide bonds exhibit two β-turns stabilized by intramolecular hydrogen bonds (38). The occurrence of intramolecular hydrogen bonds in cyclic peptides also depends on the overall backbone conformation of the peptide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conformations of cyclic hexapeptides have been studied extensively. Usually, cyclic hexapeptides acquire well-defined backbone structures and cyclic hexapeptides containing trans-amide bonds exhibit two β-turns stabilized by intramolecular hydrogen bonds (38). The occurrence of intramolecular hydrogen bonds in cyclic peptides also depends on the overall backbone conformation of the peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, cyclic hexapeptides acquire well-defined backbone structures and cyclic hexapeptides containing trans-amide bonds exhibit two β-turns stabilized by intramolecular hydrogen bonds. [36] The occurrence of intramolecular hydrogen bonds in cyclic peptides also depends on the overall backbone conformation of the peptide. Nielsen et al [37] studied cyclic hexapeptides with different number of proline residues in the peptide sequence.…”
Section: Discussionmentioning
confidence: 99%
“…These observations may indicate that the conformational flexibility of peptide 17 suggested by NMR is most likely the result of a fast interconversion process, on the NMR time scale, between type II and type I’ β‐turn populations. On the basis of metadynamics simulations, a possible mechanism for this type I’ ↔ II inter‐conversions in cyclic hexapeptides was recently reported by McHugh et al . The authors proposed a pathway that involves a shift of the β‐turn locations.…”
Section: Resultsmentioning
confidence: 99%
“…BE‐META simulations are the most effective at enhancing the conformational sampling when the slowest degrees of freedom can be identified and used as CVs. In a recent study, it was found that conformational changes of small CPs generally involve coupled dihedral changes of ϕ i and ψ i , or ψ i and ϕ i +1 , and efficient conformational sampling could be achieved by targeting these coupled two‐dihedral changes using BE‐META . Using these essential transitional motions as CVs, systematic studies of cyclic hexapeptides in explicit water were performed, leading to the identification of a sequence with a single highly populated structure …”
Section: Computational Design Of Cyclic Peptidesmentioning
confidence: 99%